The language of physics : a foundation for university study - Cullerne, John.; Machacek, Anton (Oxford : Oxford University Press, 2008)
This book introduces physics to a first year undergraduate in the language of mathematics. As such it aims to give a mathematical foundation to the physics taught at school as well as extending it to the skills and disciplines approached during a first degree course in physical science or engineering. It bridges two gaps in modern education - between the level of difficulty between A-level and undergraduate study, and between mathematics and physics. Many of the concepts are revised or introduced in the course of 'workshop' questions which are an integral part of the text. Fully explained solutions to these workshops are given as a substantial appendix to the book. The student will be enabled to study classical mechanics in terms of vector calculus, fields in terms of line and surface integrals, oscillations and waves in terms of complex exponentials and so on. As far as we are aware, this book is unique in its aim, its content, and its approach.
Includes bibliographical references and index.
1
Keywords: Mathematical physics -- Textbooks